Imaging Ischemic and Hemorrhagic Disease of the Brain in Dogs - Arnold, Susan A.; Platt, Simon R.; Gendron, Karine P.; West, Franklin D. (Frontiers in Veterinary Science, 2020)
Strokes, both ischemic and hemorrhagic, are the most common underlying cause of acute, non-progressive encephalopathy in dogs. In effect, substantial information detailing the underlying causes and predisposing factors, affected vessels, imaging features, and outcomes based on location and extent of injury is available. The features of canine strokes on both computed tomography (CT) and magnetic resonance imaging (MRI) have been described in numerous studies. This summary article serves as a compilation of these various descriptions. Drawing from the established and emerging stroke evaluation sequences used in the investigation of strokes in humans, this summary describes all theoretically available sequences. Particular detail is given to logistics of image acquisition, description of imaging findings, and each sequence’s advantages and disadvantages. As the imaging features of both forms of strokes are highly representative of the underlying pathophysiologic stages in the hours to months following stroke onset, the descriptions of strokes at various stages are also discussed. It is unlikely that canine strokes can be diagnosed within the same rapid time frame as human strokes, and therefore the opportunity for thrombolytic intervention in ischemic strokes is unattainable. However, a thorough understanding of the appearance of strokes at various stages can aid the clinician when presented with a patient that has developed a stroke in the days or weeks prior to evaluation. Additionally, investigation into new imaging techniques may increase the sensitivity and specificity of stroke diagnosis, as well as provide new ways to monitor strokes over time.